Influence of self-similarity on 3D holoscopic video coding performance - Conti, Caroline; Soares, Luís Ducla; Nunes, Paulo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
Holoscopic imaging, also known as integral imaging, is a promising solution for glasses-free 3D technology since it allows a more natural and immersive 3D sensation with continuous full motion parallax. However, in order to provide 3D holoscopic content with convenient visual quality in terms of resolution and 3D perception, ultra-high resolution acquisition and display devices are required. Consequently, efficient video coding tools become essential to deal with this large amount of data. However, current and emerging state-of-the-art video coding technologies do not yet address the specific characteristics of 3D holoscopic content. In this context, this paper presents and studies a coding scheme based on the concept of self-similarity compensated prediction, which is used to explore the particular arrangement of 3D holoscopic content through the introduction of new prediction modes. In order to profoundly analyze these new prediction modes, two different generations of video codecs, modified to handle 3D holoscopic content, are examined and compared: the first one is derived from the H.264/AVC video coding standard while the second one is based on the recent standardization project called High Efficient Video Coding (HEVC). Experimental results clearly show the advantages of using this coding scheme in both codecs, as well as the connection between the performance of the self-similarity compensation process and the characteristics of the 3D holoscopic content.